Ebselen, Iron Uptake Inhibitor, Alleviates Iron Overload-Induced Senescence-Like Neuronal Cells SH-SY5Y via Suppressing the mTORC1 Signaling Pathway - Sirirak Mukem; Ibrahim Sayoh; Saowanee Maungchanburi; Tipsuda Thongbuakaew (Hindawi Limited, 2023)
Increasing evidence highlights that excessive iron accumulation in the brain plays a vital role in neuronal senescence and is implicated in the pathogenesis of age-related neurodegenerative diseases, including Alzheimer's disease (AD) and Parkinson's disease (PD). Therefore, the chemical compounds that eliminate an iron overload may provide better protection against oxidative stress conditions that cause the accumulation of senescent cells during brain aging. Ebselen has been identified as a strongly useful compound in the research on redox biology mechanisms. We hypothesized that ebselen could alleviate an iron overload-induced oxidative stress and consequently reverses the senescence-like phenotypes in the neuronal cells. In the present study, SH-SY5Y cells were treated with ferric ammonium citrate (FAC) before ebselen, and the evaluation of the cellular iron homeostasis, the indicators of oxidative stress, and the onset of senescence phenotypes and mechanisms were carried out accordingly. Our findings showed that ebselen ameliorated the FAC-mediated iron overload by decreasing the expression of divalent metal transporter 1 (DMT1) and ferritin light chain (FT-L) proteins. In contrast, it increased the expression of ferroportin 1 (FPN1) protein and its correlation led to a decrease in the expression of the cytosolic labile iron pool (LIP). Furthermore, ebselen significantly reduced reactive oxygen species (ROS) and rescued the mitochondrial membrane potential (ΔΨm). Notably, ebselen restored the biomarkers of cellular senescence by reducing the number of senescence-associated β-galactosidase (SA-β-gal) positive cells and senescence-associated secretory phenotypes (SASP). This also suppressed the expression of p53 protein targeting DNA damage response (DDR)/p21 cyclin-dependent kinase (CDK) inhibitor through a mTORC1 signaling pathway. Potentially, ebselen could be a therapeutic agent for treating brain aging and AD by mitigating iron accumulation and restoring senescence in SH-SY5Y cells.